Increasing Meaningful Occupation for Women Who Provide Care for Their Spouse: A Pilot Study. (October 2019) - Watford, Patricia; Jewell, Vanessa; Atler, Karen
Caregiving for a loved one can be difficult and negatively affect health and quality of life. This pilot mixed-method study explored an intervention to increase participation in meaningful occupation for women who care for their spouse. Participants completed the World Health Organization Quality of Life: Brief Version (WHOQOL-BREF) and Canadian Occupational Performance Measure (COPM). The 4-week intervention consisted of an activity log (Daily Experiences of Pleasure, Productivity, and Restoration Profile) and a reflective journal (Journal of Activities and Experiences). Researchers analyzed data from the reflective journal using content analysis. Preliminary findings showed an increase in the physical health domain ( p < .05), and satisfaction with meaningful activities had clinical significance. Qualitative themes included caregiving is a demanding role, writing down experiences helped caregivers take action, and caregivers reorganized daily activities. Although preliminary results showed a positive trend, the intervention was brief, and more research is needed to determine whether greater gains are possible, and can be sustained.